Aphis spiraephaga n. sp., eine in Mitteleuropa häufig an Spiraea auftretende Blattlaus (Homoptera: Aphididae). - Müller, Fritz Paul (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Aphis spiraephaga n. sp. is a dark brown aphid covered with wax powder and living on Spiraea spp. It has proved a common species widely distributed over Central Europe. Although it has distinct characters of a nonmigrating aphid the oviparous females are the progeny of alatae. The males are alate and of emeraldine ground colour. The main distinguishing characters in comparison to similar looking species and to North American Aphis-species living an Spiraea are noted. Nomenclatural Acts spiraephaga Müller, 1961 (Aphis), spec. n.